(untitled) (Namibian Journal for Research, Science and Technology, 2022)
Despite the intervention strategies that have been put in place to fight poverty, Namibia continues to experience prevalence of poverty with large numbers of households still living in poverty conditions and unable to afford the minimum daily essentials for a decent life. In this quantitative cross-sectional study design, the impact of sociodemographic characteristics of households on their poverty levels was statistically analysed using an ordered probit regression on data from the 2015/16 Namibia household income and expenditure survey. Results showed that sociodemographic characteristics such as the types of household dwelling unit, highest education attainment of the head of household, household main language, household tenure and household main source of income had a significant impact on the household’s poverty levels. Households living in a mobile home dwelling unit, whose heads had secondary education as their highest educational attainment as well as households that were mortgaged and whose main source of income were from other sources were less likely to be severely household poor and more likely to be household poor. Furthermore, households living in a singlequarters dwelling unit and whose main language were Setswana were more likely to be severely household poor and less likely to be household poor. It is therefore recommended that the Namibian government and policy makers put more efforts in improving the sociodemographic characteristics of households, particularly those living in a single quarter dwelling unit and whose main language were Setswana.